1991
DOI: 10.1007/bf01235548
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic innervation of the dorsal horn of rat spinal cord: light and electron microscopic immunocytochemical study

Abstract: The ultrastructure of serotonergic projections to the dorsal horn of the rat spinal cord has been investigated, using a highly specific polyclonal antiserum. The highest concentrations of immunoreactive profiles were found in lamina I and the outer part of lamina II (IIo). Intermediate concentrations were found in laminae III and IV, while the inner part of lamina II (IIi) was almost devoid of immunoreactivity. Whereas 60% of the profiles show at least one varicosity studded with synaptic vesicles, only one-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(59 citation statements)
references
References 51 publications
5
54
0
Order By: Relevance
“…1E) and it is also well established that the descending serotonergic inhibitory pathways participate in the inhibition of pain transmission at the spinal level [32][33][34][35]. In our data, unlike the GABA receptor antagonist, methylsergide, the serotonin receptor antagonist did not show a significant effect on tactile sensitivity (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…1E) and it is also well established that the descending serotonergic inhibitory pathways participate in the inhibition of pain transmission at the spinal level [32][33][34][35]. In our data, unlike the GABA receptor antagonist, methylsergide, the serotonin receptor antagonist did not show a significant effect on tactile sensitivity (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…To date, three 5-HT subtypes have been detected in the spinal network involved in ejaculation. 5-HT1A, -1B, and -2C receptors are densely expressed in the sacral parasympathetic nucleus and motoneurons of Onuf's nucleus (Marlier et al, 1991;Thor et al, 1993;Ridet et al, 1994;Bancila et al, 1999). In addition, high density of 5-HT1B receptors has been described in lamina X of the lumbar spinal cord, which includes SGE area (Marlier et al, 1991).…”
Section: B Spinal Cordmentioning
confidence: 93%
“…5-HT1A, -1B, and -2C receptors are densely expressed in the sacral parasympathetic nucleus and motoneurons of Onuf's nucleus (Marlier et al, 1991;Thor et al, 1993;Ridet et al, 1994;Bancila et al, 1999). In addition, high density of 5-HT1B receptors has been described in lamina X of the lumbar spinal cord, which includes SGE area (Marlier et al, 1991). After a series of experiments investigating the role of 5-HT in a model of expulsion reflex in rat (urethrogenital reflex), it was suggested that 5-HT released in lumbosacral segments from terminals of neurons lying in the ventrolateral medulla exerts an inhibitory tone on ejaculation McKenna, 1990, 1992;Gravitt and Marson, 2007).…”
Section: B Spinal Cordmentioning
confidence: 99%
“…Indeed most 5HT varicosities establish nonsynaptic contacts with dorsal horn neurons (Marlier et al, 1991;Ridet et al, 1993). Even though some 5HT neurons clearly act via conventional synapses (Jankowska et al, 1995;Maxwell and Jankowska, 1996), there appears to be a predominant nonsynaptic "volume transmission" mechanism that operates (Fuxe and Agnati, 1991).…”
Section: Technical Considerationsmentioning
confidence: 99%